The adoption reunion handbook - Trinder, Liz.; Feast, Julia; Howe, David, 1946- (Hoboken, N.J. : John Wiley & Sons, 2004)
"Based on a large-scale research study, the auctors Liz Trinder, Julia Feast and David Howe have drawn on the real-life experience of adopted people who have searched for, and had a reunion with, birth relatives." "This 'how to' guide is essential for everyone involved, particularly those considering searching for information on their birth relatives. It will also be of use to birth parents, adoptive parents, adoption charities, social workers, psychologists and counsellors."--BOOK JACKET.
Introduction -- Taking the first step: birth record information -- On the search trail -- Reunions with birth mothers -- Reunions with birth fathers -- Reunion with siblings -- The adoptive family and reunion -- Rejection and reunions that break down -- The search and reunion journey -- Appendix 1: Information on search and reunion in the UK, Ireland, Australia, New Zealand, Canada, and USA -- Appendix 2: Further reading.
Includes bibliographical references (p. 153-154) and index.
Keywords: Adoptees -- Great Britain -- Identification -- Handbooks, manuals, etc; Birthparents -- Great Britain -- Identification -- Handbooks, manuals, etc; Public records -- Great Britain -- Handbooks, manuals, etc; Adoption -- Great Britain -- Psychological aspects